1973
DOI: 10.1002/pol.1973.180110512
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of injection‐molded polypropylene

Abstract: A surface zone composed of at least three distinct layers has been detected in injection‐molded polypropylene. The morphology of these layers as determined by optical and scanning electron microscopy forms a continuous picture from the “as‐molded” surface to the core. With the exception of the first layer which is always featureless, the observed morphology is mostly spherulitic. Starting in the second layer, the spherulites decrease steadily in size until they reach a minimum somewhere near the middle of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(34 citation statements)
references
References 19 publications
3
31
0
Order By: Relevance
“…Even though new technologies have been developed to improve the use of metallic pigments in polymers, there is still no deep analysis of the effect of the addition of these particles in the morphological and mechanical performance of PP injected parts. Melt temperature and mold temperature affect the temperature gradient and shear rate, two variables which are inherent to the injection-molding process and which are expected to influence crystallization and polypropylene morphology [24]. Viana et al [25] identified the significant processing variables affecting the development of the morphological parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Even though new technologies have been developed to improve the use of metallic pigments in polymers, there is still no deep analysis of the effect of the addition of these particles in the morphological and mechanical performance of PP injected parts. Melt temperature and mold temperature affect the temperature gradient and shear rate, two variables which are inherent to the injection-molding process and which are expected to influence crystallization and polypropylene morphology [24]. Viana et al [25] identified the significant processing variables affecting the development of the morphological parameters.…”
Section: Introductionmentioning
confidence: 99%
“…For scanning electron microscopy (SEM), the films stripped from the glass slides were etched in a solution containing 20-% sulfuric acid saturated with chromium trioxide for 5 min at 70 oc. 9,to…”
Section: Materials and Preparationmentioning
confidence: 99%
“…Because of the different thermomechanical history the melt undergoes, the injection-molded parts often show a hierarchical multilayered structure through the thickness [1][2][3][4][5][6][7][8][9]. For the universal semicrystalline polymer, Polypropylene (PP), this layered structure has been widely studied with its heterogeneous crystallization because of the shear and temperature gradient [10][11][12][13][14][15][16][17][18][19]. It has been reported that the injection-molded PP parts often show three distinct crystalline zones: a highly oriented nonspherulitic skin, a shear zone with molecular chains oriented essentially parallel to the injection direction, and a spherulitic core with essentially no preferred orientation, respectively [10].…”
Section: Introductionmentioning
confidence: 99%